Relationship Between Nursing Students' Attitudes Toward Elderly Discrimination and Opinions About Home Care Services. Issue 4 (November 2019) - Meriç, Meltem; Ergün, Gül; Pola, Ganna; Dölek, Meral; Totur Dikmen, Burcu; Dal Yılmaz, Ümran
The determination of nursing students' attitudes toward elderly discrimination and their opinions about home care is important in that it will affect the quality of care provided to elderly individuals in their homes by the students in the future. For this reason, the aim of this study was to determine relationship between nursing students' attitudes toward elderly discrimination and their opinions about home care services. This descriptive study was conducted with a total of 318 students from a university nursing faculty during the fall semester of the 2016-2017 academic year. Data for the study were collected using the Home Care Services Evaluation Questionnaire and the Ageism Attitude Scale. It was found that there was a positively significant but weak relationship between the students' age discrimination scale total score and the positive discrimination subdimension score, and their opinions about home care services ( p < .001). Students' attitudes toward elderly discrimination were found to make a statistically significant contribution to their opinions about home care services. It was ascertained that students' attitudes toward elderly discrimination affected their opinions about home care services. It is recommended that geriatric nursing and home care nursing lectures be included in the nursing education curriculum, awareness of the importance of the concept of old age and elderly care be increased by establishing internship fields for students in institutions that provide home care for the elderly, and positive attitudes toward the elderly be promoted.